Effectiveness of Non-Pharmacological Interventions in the Enhancement of Quality of Life in Infertile Women: A Scoping Review - Zeinab Hamzehgardeshi; Forouzan Elyasi; Mahmood Moosazadeh; Imaneh Ahmadi; Maryam Ahmadian; Fatemeh Ansari (Mazandaran University of Medical Sciences, 2021)
Introduction and purpose: Infertility and its related factors are among the conditions affecting and reducing the quality of life in both physical and psychological dimensions. Given the critical importance of the role played by the quality of life in the success of treatment, the present study aimed to assess the non-pharmacological interventions made to improve the quality of life among infertile women. Methods: A systematic search was conducted on Scientific Information Database, including MagIran, Google Scholar, PubMed, ScienceDirect, Embase, Scopus, and IranMedex from 2010- 2021. Data were extracted from all the studies that met the eligibility criteria based on the aims of the study. A total of 23 related articles were extracted and used. The quality of the articles was assessed based on the Risk of bias Cochrane. Results: A total of 23 articles met the eligibility criteria for a scoping review, 11 studies were published within the last five years, and 13 articles were performed In Iran. Psychological interventions were the most studied, and  15 (65.2%) evaluated studies included multilateral interventions (6;26%)  and complementary interventions (2; 8.6%). The majority of interventions improved the quality of life among the studied participants. In this study, the highest risk of bias was related to performance and detection, and the lowest number of articles were related to detection bias. Conclusion: The majority of non-pharmaceutical interventions, especially in the field of psychology, are effective in the enhancement of infertile women's quality of life. Therefore, it is suggested that special attention be devoted to effective counseling services and planning, along with common infertility treatments, to improve their quality of life. Nevertheless, more culture-based research is required to make more effective interventions and change the policies.